Physical activity and body composition in patients with rheumatoid arthritis - O. V. Dobrovolskaya; N. V. Toroptsova; A. Yu. Feklistov; N. V. Demin; O. A. Nikitinskaya (Современная ревматология, 2022)
Objective: to evaluate physical activity (PA) and its relationship with body composition in patients with rheumatoid arthritis (RA).Patients and methods. The study included 93 women with RA. A standardized questionnaire survey, anthropometric measurements, laboratory work up, and dual-energy x-ray absorptiometry were conducted to assess body composition and bone mineral density. The level of PA was determined using the International Physical Activity Questionnaire (IPAQ).Results and discussion. The IPAQ survey showed that 46 (49.5%), 41 (44.1%) and 6 (6.4%) patients had high, moderate and low levels of PA, respectively. The patients did not differ in clinical and anamnestic, laboratory and instrumental data depending on the level of PA. Correlations were found between total energy expenditure by IPAQ and daily food calcium intake (r=0.26, p=0.012), shoulder circumference (r=0.22, p=0.042) and postmenopausal duration (r=-0.27, p=0.016). The relationship between the sarcopenic phenotype (SP) and the time of vigorous physical activity less than 15 minutes per day was revealed (odds ratio, OR 6.31; 95% confidence interval, CI 1.75–22.71; p=0.004), between the frequency of moderate physical exercise and walking less than 4 times a week (OR 4.09; 95% CI 1.16–14.47; p=0.027 and OR 4.73; 95% CI 1.24–18.07; p=0.021, respectively), the presence of osteoporosis – OD (OR 9.41; 95% CI 2.73–32.47; p <0.001). The risk of obesity increased with vigorous exercise less than 15 minutes per day (OR 3.03; 95% CI 1.11–8.29; p=0.029). The osteoporotic phenotype (OPP) was associated with patient age (OR 1.12; 95% CI 1.05–1.19; p=0.001) and the presence of SP (OR 8.97; 95% CI 2.39– 33.60; p=0.001).Conclusion. Half of the patients had moderate and low level of PA, independent of age, RA duration and activity. SP was associated with insufficient PA and the presence of OPP. Obesity is also associated with lack of PA, while OPP is associated with age and the presence of SP.